Transformation composition – property dependencies of binary homogeneous mixtures - L. A. Serafimov; V. M. Raeva (Тонкие химические технологии)
The possible transformations of composition – property dependencies of binary homogeneous mixtures are considered. Transformations of the first multiplicity leading to the emergence of internal singular points are followed by changes in the types of points: the topological minimum becomes topological maximum (and vice versa). Transformations of the second multiplicity are related to the existence of internal complex singular points, which are the inflection points of composition – property dependencies of binary mixtures.